PENGARUH MODEL PEMBELAJARAN EVERYONE IS A TEACHER HERE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS VI SD NEGERI 095550 JL. ASAHAN KM 4 - Maya Sari Lumban Gaol, Rezka; Simanjuntak, Melvin M.; Sabrina Sibarani, Imelda (STKIP Subang, 2026)
This study aims to determine the effect of the Everyone Is A Teacher Here learning model on the science learning outcomes of sixth-grade students of SD Negeri 095550 Jl. Asahan Km. 4. This study uses a quantitative approach with an Pre-Experimental Design type and One Group Pretest-Posttest Design. The research sample consisted of 22 students. Data collection techniques were carried out through pretest and posttest, then analyzed using the Shapiro-Wilk normality test and paired sample t-test with the help of SPSS version 26. The results of the study showed an increase in student scores after the implementation of the Everyone Is A Teacher Here learning model. The results of the normality test showed that the data was normally distributed with a pretest significance value of 0.227 and a posttest of 0.130. Furthermore, the results of the paired sample t-test obtained a significance value of 0.000 <0.05, so Ha was accepted and H0 was rejected. Thus, it can be concluded that the Everyone Is A Teacher Here learning model has a significant effect on the science learning outcomes of sixth-grade students of SD Negeri 095550 Jl. Asahan Km 4